A review of the application of reinforced hydrogels and silk as biomaterials for intervertebral disc repair - DA Frauchiger (European Cells & Materials, 2017)
The degeneration of the intervertebral disc (IVD) within the spinal column represents a major pain source for many patients. Biological restoration or repair of the IVD using “compressive-force-resistant” and at the same time “cytocompatible” materials would be desirable over current purely mechanical solutions, such as spinal fusion or IVD implants. This review provides an overview of recent research on the repair of the inner (nucleus pulposus = NP) and the outer (annulus fibrous = AF) parts of the IVD tissue. Many studies have addressed NP repair using hydrogel-like materials. However, only a few studies have so far focused on AF repair. As the AF possesses an extremely low self-healing capacity and special attention to shear-force resistance is essential, special repair designs are required. In our review, we stated the challenges in IVD repair and highlighted the use of composite materials such as silk biomaterials and fibrin cross-linked reinforced hydrogels. We elaborated on the origin of silk and its many in tissue engineering. Furthermore, techniques such as electrospinning and 3D printing technologies allow the fabrication of versatile and functionalised 3D scaffolds. We summarised the research that has been conducted in the field of regenerative medicine over the recent years, with a special focus on the potential application and the potential of combining silk and reinforced – and thus mechanically tailored – hydrogels for IVD repair.